First-principles study on the structure, fracture toughness, and thermodynamic properties of a new-designed Co30Ni30 Fe20Cr20 high-entropy alloy - Huiqi Xie; Xiaofeng Li; Xu Wang; Touwen Fan; Denghao Yi; Yuankui Cao; Xiaohui Yang; Bin Liu; Peikang Bai (Journal of Materials Research and Technology, 2022)
In this work, the structural stability, fracture toughness, and thermodynamic properties of Co30Ni30Fe20Cr20 high-entropy alloy (HEA) has been investigated by using first-principles calculations combined with special quasi-random structures. The calculated lattice constant of 3.485 Å was in good agreement with the experiments, and the obtained formation enthalpy value of −1.17 eV/atom indicated that this particular HEA was stable. The results showed that the Fracture energy of the [111] direction was much lower than the [001] and [110] directions. Therefore, the bond strength of the [111] direction was inferred to be the weakest. Finally, the entropy, internal energy, and specific heat capacity of the Co30Ni30Fe20Cr20 HEA increased with increasing temperature, while the free energy and bulk modulus decreased. Thus, the results obtained in this work could be used for studying and designing high performance CoCrFeNi HEAs.